Associations of stigma, loneliness, and treatment self-regulation with HIV medication adherence among individuals with substance use disorder using a mobile health application - Tarfa, Adati; Verinumbe, Tarfa; Yang, Fan (Ellie); Shiyanbola, Olayinka O.; Liebert, Cameron; Dietz, Sarah; Miller, Rebecca; Westergaard, Ryan P. (Frontiers in Public Health, 2024)
Introduction: Medication adherence contributes to poor HIV outcomes, especially among people with HIV and Substance use disorder (SUD). Mobile health applications have been leveraged to improve behavioral health outcomes among this population. Our crosssectional study examined the relationship between medication adherence with factors such as treatment self-regulation, isolation, and internalized stigma, among people with HIV and SUD using the Addiction Comprehensive Health Enhancement Support System (A-CHESS) mobile app.Methods: A sample of 208 participants using A-CHESS to improve treatment adherence completed a survey. Adherence was measured using the Four-item Morisky Medication Adherence Scale and dichotomized (maximum score of 20 points considered as adherent). Positive and negative affect was measured separately using Positive Affect Negative Affect Schedule and loneliness was measured using UCLA 3-item Loneliness Scale. Internalized stigma was measured using Internalized AIDS-Related Stigma Scale. Competence/Treatment self-regulation was measured using Treatment Self-regulation Questionnaire. Multivariable logistic regression was used to assess the associations of affect, treatment self-regulation, isolation, and internalized stigma, with adherence to antiretroviral therapy adjusting for age, education, and gender.Results: Among 208 participants in this study, most were Black (n=137; 66%), male (n=156; 75%) and had a mean age of 46 (standard deviation = 11.3). The most reported substances associated with missing HIV medication were alcohol (27%) and cocaine/crack (20%). Logistic regression analysis revealed that internalized stigma was significantly associated with HIV medication adherence (OR = 0.82; 95%CI: 0.70 -0.99; p = 0.034).Internalized stigma was significantly associated with HIV medication adherence. Further research is needed to better understand this relationship and develop interventions addressing stigma in people with HIV and SUD.